EKSISTENSI PENGADILAN HAM DALAM PENYELESAIAN KASUS PELANGGARAN HAM - Gracesy Prissela Christy; Edmondus Sadesto Tandungan (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2023)
The issue of upholding human rights always goes hand in hand with the issue of law enforcement, where this is one of the crucial things that is most often complained about by citizens at the moment. Namely weak law enforcement. The application of law to human rights violations in Indonesia is guided by Law no. 26 of 2000 concerning Human Rights courts, where in this law it is stated about ad hoc courts which are used to try human rights violators in Indonesia. The aim of this research is to find out the role of human rights courts in resolving human rights violations. The method used is a research method using normative legal research methods. The research results show that the Human Rights Court is a tool that can be used to resolve cases of human rights violations, especially serious human rights violations. The Human Rights Court has the authority to examine and decide cases of human rights violations, including settling cases involving compensation, restitution and rehabilitation in accordance with statutory regulations.